2009
DOI: 10.1007/s00395-009-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Reference change values and determinants of variability of NT-proANP and GDF15 in stable chronic heart failure

Abstract: Biovariability, reference change values (RCV), and index of individuality (IOI) have not been previously described for NT-proANP or GDF15. Also, the relation of changes of these markers to other clinical variables or biomarkers is unknown. In 41 patients with stable chronic systolic dysfunction, NT-proANP and GDF15 were measured alongside with clinical variables/markers comprising NT-proBNP, hsTnT, and hsCRP at four sampling intervals (2 weeks, 1-, 2-, 3-month intervals). At 2 weeks, 1-, 2-, and 3-month-follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Cox-proportional hazards models evaluated the association of 12-month relative change of ln GDF-15 (continuous and categorical) with a secondary CVE and total mortality during the subsequent 9 years of follow-up. Categorical analysis shows an upper category including those with a 12-month relative change Ն20%, a reference group including those with a relative change Ͻ20% but ϾϪ20%, and a lower category for those with a relative change ՅϪ20% (14 ). We adjusted initially for baseline levels of ln GDF-15, age and sex (Model 1), followed by additional adjustment for well-established cardiovascular risk factors (Model 2), and further adjustment for biomarkers representing specific pathogenetic pathways: ln NT-proBNP, ln hs-CRP, and ln hs-cTnT (Model 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cox-proportional hazards models evaluated the association of 12-month relative change of ln GDF-15 (continuous and categorical) with a secondary CVE and total mortality during the subsequent 9 years of follow-up. Categorical analysis shows an upper category including those with a 12-month relative change Ն20%, a reference group including those with a relative change Ͻ20% but ϾϪ20%, and a lower category for those with a relative change ՅϪ20% (14 ). We adjusted initially for baseline levels of ln GDF-15, age and sex (Model 1), followed by additional adjustment for well-established cardiovascular risk factors (Model 2), and further adjustment for biomarkers representing specific pathogenetic pathways: ln NT-proBNP, ln hs-CRP, and ln hs-cTnT (Model 3).…”
Section: Discussionmentioning
confidence: 99%
“…This change criterion was chosen because it approximated a normal distribution to a greater extent than other relative or absolute change criteria (Shapiro-Wilk W-test statistic ϭ 0.95). Second, we defined different change patterns considering published data on the biological variability of GDF-15 (17 ): decreasing, change in GDF-15 concentrations ՅϪ20%; increasing, change in GDF-15 concentrations Ն40%; or unchanged, change in GDF-15 concentrations between Ϫ19% and 39%. Independent predictors of changes were identified by multiple linear regression analysis and multivariable regression analysis, as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the intraindividual biological variation of GDF-15 in patients with clinically stable chronic HF is lower compared with the intraindividual biological variation of the natriuretic peptides, 36,37 which may facilitate interpretation of temporal changes in GDF-15 in HF. Previous studies using echocardiography or repeat measurements of BNP found no evidence for a progressive worsening of cardiac function in patients from the Val-HeFT trial over the course of 12 months; in fact, slight improvements in LVEF and decreases in left ventricular internal diastolic dimension corrected for body surface area and BNP have been reported.…”
Section: Repeat Measurement Of Gdf-15 and Outcome In Hfmentioning
confidence: 99%